La escritura de Ricardo Piglia: los rastros de una pesquisa - Casarin, Marcelo (Anales de Literatura Hispanoamericana, 2008)
This article surveys the most important books of the Argentine writer Ricardo Piglia (1940) and puts emphasis on to what an extent his novels or essays may be considered a vast territory of autotextuality. Besides, this article intends to demonstrate that in the texts of this Argentine narrator there exists a writing procedure which is paramount with respect to the others and overdetermines both narrations and essays; this is the "chase" procedure: a research work which orientates writing and at the same time turns itself into a heuristic and interpreting reading program and approaches Piglia´s work into the detective story tradition.